The communicative power of trade unionism: labour law, political opportunity structure and social movement strategy; Die kommunikative Kraft der Gewerkschaftsbewegung: Arbeit Recht, politische Opportunitaẗsstruktur und soziale Bewegungsstrategie - Gregoris Ioannou (Industrielle Beziehungen, 2020)
This article argues that more emphasis should be paid to the communicative power of trade unionism because it may constitute a starting point or a privileged standpoint which a trade union may use to counter its weakness regarding its other sources of power. Reviewing the trade union revitalisation literature, it is argued that social movement theory in general and especially 'political opportunity structure', can complement and enrich the power resources approach which is a useful tool in the analysis of trade union action. The case study of a weak trade union winning a strike largely as a result of its successful utilisation of its communicative power is presented where the public communication of the two sides to the conflict is subjected to content and discourse analysis. The article argues that trade unions can enhance their position through the adaptation of social movement strategy and campaign tactics into trade union activity because social movements are more accustomed to orienting their action in the public sphere. In this effort trade unions may draw upon the more explicitly normative and substantive dimension of labour law as a resource to legitimise and garner support for the unions' objectives framing in a more expansive manner the issues at stake so that a significant section of society can identify with the trade union struggle at hand. – – Der Beitrag argumentiert fur̈ eine star̈kere Beruc̈ksichtigung kommunikativer Machtressourcen in der Gewerkschaftsbewegung, um eventuelle Schwac̈hen in Bezug auf andere Machtquellen auszugleichen. Auf Basis einer Literaturrecherche zur gewerkschaftlichen Revitalisierung wird argumentiert, dass die Theorie der sozialen Bewegungen im Allgemeinen sowie der "Political-Opportunity-Ansatz" im Besondern, den in der Gewerkschaftsforschung bewaḧrten Machtressourcenansatz ergan̈zen und bereichern kon̈nen. Es wird der Fall einer schwachen Gewerkschaft vorgestellt, die einen Streik vor allem aufgrund der erfolgreichen Nutzung ihrer kommunikativen Ressourcen gewinnen konnte. Die Studie fokussiert auf die of̈fentliche Kommunikation der Konfliktparteien und unterzieht sie einer Inhalts- und Diskursanalyse. Es wird argumentiert, dass Gewerkschaften ihre Position durch die Anpassung an die Strategien sozialer Bewegungen und deren Kampagnentaktik verbessern kon̈nen, da soziale Bewegungen eher daran gewoḧnt sind, ihr Handeln am of̈fentlichen Diskursraum auszurichten. Bei diesen Bemuḧungen kon̈nen Gewerkschaften die explizit normative und inhaltliche Dimension des Arbeitsrechts als Ressource nutzen, um ihre Ziele zu legitimieren und zu unterstuẗzen. Durch ein umfassenderes Framing gewerkschaftlicher Anliegen im Arbeitskampf kann eine star̈kere Identifikation gros̈serer Teile der Gesellschaft mit gewerkschaftlichen Zielen erreicht werden.
Keywords: J51; J52; J83; 330; trade unionism; power sources; communication strategy; labour law; strikes; Gewerkschaftsbewegung; Machtressourcen; Kommunikationsstrategie; Arbeitsrecht; Streiks